(untitled) (Spectrum of Humanities and Social Sciences, 2025)
Senior citizens possess the traditional knowledge of cultural values and skills, and they are instrumental in transferring them to the youth. However, modernization, migration and strict government rules are making it increasingly difficult to preserve knowledge of the ancient practices. This paper examines the life and lived experiences of five elderly (participants) from five different communities (Brahmin, Lama, Muslim, Tharu and Gurung) in Surkhet District Nepal. The rational of the study is based on Cultural Transmission theory. The findings demonstrate that migration, non-supportive attitude of the institutions and the rules such as Samudayik Ban (Community Forest law) have made it difficult to conserve this knowledge. On the other hand, community activities such as homestays and cultural events help to keep the knowledge alive. Valuing the elders in school and building strong social connections are immensely essential to transfer their knowledge to younger ones in Nepal. The study also emphasizes the importance of policy change and official recognition of elders as culture bearers in line with the Constitution of Nepal and the United Nations Educational, Scientific and Cultural Organization’s guidelines to protect cultural heritage.